The Effect of Using Audiovisual Media on Learning Outcomes of Citizenship Education Subjects in Class 3 Elementary Schools: Pengaruh Penggunaan Media Audiovisual Terhadap Hasil Belajar Mata Pelajaran Pendidikan Kewarganegaraan Kelas 3 Sekolah Dasar - Ananda, Vinkania; Tirtoni, Feri (Indonesian Journal of Education Methods Development, 2023)
The research entitled the effect of the use of audiovisual media on learning outcomes for the third grade Civics subject at SDN Sugiwaras Candi. This study aims to determine how much influence the use of audiovisual media has on the learning outcomes of third grade students of SD Negri Sugihwaras Candi. This research uses Pre- Experimental Design and One Group Pretest-Posttest Design. The research instrument used in the form of Pretest - Posttest with a population of 26 students. In this research, the sampling technique used is saturated sample. Prior to the data analysis technique, it is necessary to test the validity and reliability test to determine whether the research instrument used can be declared valid and reliable or not. Based on this, in this study, the validity and reliability tests were carried out by two experts. The data analysis technique used in this research is the t-test paired sample t-tets. Based on the normality test, it is known that the pretest is 0.126 while the posttest is 0.122. Because the significance for the difference in variables is greater than 0.05 it can be concluded that the data on the variables are normally distributed. The data analysis technique in the t-test is known that the paired sample t-test table shows a significance value (2-tailed) 0.000 <0.05. The results of data analysis show that audiovisual media can increase the value of understanding in student learning outcomes. This shows that there is a significant difference in the effect of using audiovisual media on student learning outcomes at SDN Sugiwaras Candi Sidoarjo.